12 Self-help for medically unexplained symptoms: a systematic review and meta-analysis. Issue 8 (13th July 2017) - Gils, Anne van; Schoevers, Robert A; Bonvanie, Irma J; Gelauff, Jeannette M; Roest, Annelieke M; Rosmalen, Judith GM
Abstract : Objective: Medically unexplained symptoms (MUS), which are highly prevalent in all fields of medicine, are difficult to treat. Psychological treatments have shown modest effects, but these are costly, time consuming, and not easily accessible. Self-help interventions might overcome these barriers. The primary aim of this systematic review and meta-analysis was to assess the efficacy of self-help interventions for adults with MUS. Method: Relevant studies were identified by searching electronic databases (PubMed, Embase, PsycINFO, and CINAHL from inception to May 2014) and scanning reference lists of included articles and related reviews. Two researchers independently selected randomised controlled trials comparing self-help to usual care or waiting list in adults with MUS. Data were extracted independently by two researchers using standardised forms. Standardised mean differences (Hedges' g) were pooled using a random-effects model. Studies were critically appraised using the Cochrane 'risk of bias assessment tool'. Outcomes were symptom severity and quality of life directly post-treatment and at follow-up. Results: Out of 582 studies identified, 18 studies met all inclusion criteria. Studies were heterogeneous with regard to patient populations, intervention characteristics, and outcome measures. Compared to usual care or waiting list, self-help was associated with lower symptom severity (17 studies, n=1894, g=0.58, 95% CI 0.32–0.84, p<0.001) and higher QoL (16 studies, n=1504, g=0.66, 95% CI 0.34–0.99, p<0.001) directly post-treatment. Similar effect sizes were found at follow-up. A high risk of bias was established in the majority of included studies. However, sensitivity analyses suggested that this did not significantly influence study results. Funnel plot asymmetry indicated potential publication bias. Conclusion: Self-help is associated with a significant reduction in symptom severity and improvement of QoL. Due to the suboptimal methodological quality of the majority of included studies, further research is needed to confirm the findings of this study. For future studies we recommend the use of uniform and validated measurement instruments, inclusion of follow-up assessments, and performance of intention-to-treat analyses.